X-ray diffraction investigation of GaN layers on Si(111) and Al₂O₃ (0001) substrates - Safriuk, N.V.; Stanchu, G.V.; Kuchuk, A.V.; Kladko, V.P.; Belyaev, A.E.; Machulin, V.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Methodical approaches to the analysis of X-ray data for GaN films grown on
various buffer layers and different substrates are presented in this work. Justification of
dislocation structure investigation by various methods was analyzed and approaches for
evaluation of deformation level and relaxation are discussed. Clarity and accuracy of
obtained structure characteristics of nitride films are under discussion. Optimization
methods for experimental data processing are shown. Structural properties were obtained
using high resolution X-ray diffraction with two types of scans and
reciprocal space maps. Microscopic nature of spatial inhomogeneities in these structures
(deformations and dislocation density) and influence of the buffer layer thickness on
properties of GaN layer were discussed with account of obtained results.